Globalization and the environment of China - Yang, Boqiong; Bu, Maoliang (Emerald, 2014)
This book is timely in its investigation of the environmental influence of globalization and China. Volume 14 focusses on : theoretic modeling of environmental impact of foreign direct investment (FDI) on host countries, international openness and corporate environmental performance in China, environmental regulation and Chinese firm productivity, industrial sector data in China, environmental impact of foreign vs. domestic capital investment in China, globalization and climate change and new empirical panel data evidence This book answers the following questions : does FDI affect the environment of host countries? How international openness influences China's corporate environmental performance? Is lax environmental regulation attractive for multinationals to invest in China? The impact of corporate social responsibility on multinationals? Does FDI play a role trade and ISO14001 certification? Can rigorous environmental regulation enhance Chinese firm productivity? Does FDI concentrate in pollution intensive sectors in China? Is globalization good or bad for climate change? How does FDI and social corporate responsibility stack up against the pollution haven hypothesis?
Keywords: elektronické knihy; electronic books; Globalization -- Economic aspects -- China.; Global environmental change.; China -- Economic conditions -- 2000-